\(x+y=1\Rightarrow x=1-y\)
\(A=x^3+y^3+xy\)
\(=\left(x+y\right)\left(x^2-xy+y^2\right)+xy\)
\(=x^2+y^2\) (vì x + y = 1)
\(=\left(1-y\right)^2+y^2\)
\(=2y^2-2y+1\)
\(=2\left(y^2-y+\frac{1}{4}\right)+\frac{1}{2}=2\left(y-\frac{1}{2}\right)^2+\frac{1}{2}\ge\frac{1}{2}\forall y\)
Dấu "=" xảy ra khi: \(y-\frac{1}{2}=0\Rightarrow y=\frac{1}{2}\Rightarrow x=1-y=\frac{1}{2}\)
Vậy GTNN của A là \(\frac{1}{2}\)khi \(x=y=\frac{1}{2}\)
\(A=x^3+y^3+xy=\left(x+y\right)\left(x^2-xy+y^2\right)+xy\)
\(=x^2-xy+y^2+xy=x^2+y^2\ge\frac{\left(x+y\right)^2}{2}=\frac{1}{2}\)
Nên min A là \(\frac{1}{2}\) khi \(x=y=\frac{1}{2}\)